Proceedings of the International Conferences on Educational, Social Sciences and Technology - ICESST 2018 2018
DOI: 10.29210/2018134
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between self-control and peer conformity with smoking behavior

Abstract: This research based on students of smoking behavior that unusual, smoking behavior is perceived as self-identity. However, students at senior high school level have great potential to be addicted to cigarettes.The low ability students in self-control and strength of peer conformity is the most dominant factor in influencing the smoking behavior of students. This study aims to describe self-control, peer conformity, smoking behavior, and the relationship of self-control andpeers conformity with smoking behavior… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 3 publications
(3 reference statements)
1
5
0
2
Order By: Relevance
“…Another study also examined the relationship between peer conformity and the intention of smoking among adolescents. Smoking adolescents had less self-control to conduct and justify the situations of the social environment (Fauzan, Firman, & Daharnis, 2018). Peer conformity is identical to the closeness of the adolescent with the members of their social peer group.…”
Section: Discussionmentioning
confidence: 98%
“…Another study also examined the relationship between peer conformity and the intention of smoking among adolescents. Smoking adolescents had less self-control to conduct and justify the situations of the social environment (Fauzan, Firman, & Daharnis, 2018). Peer conformity is identical to the closeness of the adolescent with the members of their social peer group.…”
Section: Discussionmentioning
confidence: 98%
“…6 Adolescent self-control has a negative and significant relationship with adolescent smoking behavior. 7,8 The adolescent's behavior will continue to increase in accordance with its development stage which is characterized by increasing frequency and intensity of smoking and often results in nicotine dependence. Teenagers start smoking at the instigation of themselves because they want to try.…”
Section: Introductionmentioning
confidence: 99%
“…In the same direction, the variety of risk factors associated with reduced self-control identified in this study, represent the importance and complexity of setting priorities for interventions involving adolescent health prevention (Davies et al, 2017;Walters et al, 2018). Similar results were presented by studies that demonstrated low levels of self-control in adolescents in relation to multiple risk factors (de Winter et al, 2016), alcohol use (Bobrowski, 2019;Wills et al, 2016), binge drinking , victimization by violence (Davis et al, 2017), tobacco use (Fauzan et al, 2018;Holmes, 2018) and alcohol use associated with premature sexual activity in adolescents (Agbaria et al, 2017).…”
Section: Discussionsupporting
confidence: 79%